Love/Hate to Florence in Giovanni Agnoloni’s Novels: La Casa Degli Anonimi and Berretti Erasmus - Kopańska, Karolina (Contrasts in humanities: literature, language, culture, 2023)
In this article the author examines the heroes’ relations with the city – Florence in Giovanni Agnoloni’s novels: La casa degli anonimi and Berretti Erasmus. Emanuela and Aurelio’s destinies (Casa degli anonimi) cross in a surreal night pursuit along Florence streets. They had long thought of escaping the city inhabited by hostile Florentines. Giovanni (Berretti Erasmus), a law student from the 2000s participates in an Erasmus project in England. During that experience, he understands that his destiny will be linked to elsewhere. He will undertake numerous journeys for study or work reasons in the United Kingdom, Holland, Lithuania, Ireland, and Poland. The cyclical returns to the beloved-hated Florence will be a source of oxygen and suffering for him. In the first part, the author of the article presents the issues related to the city’s periphery. In the second part, she describes the nature of the Florentines. In the third part, she focuses on the process leading to the decision to leave the city and she describes the moment of the turning point.